Perspectives of residents, students and faculty about residents as teachers at a University Hospital in Karachi - Raza, Mahanoor; Madhwani, Akber; Jehan, Fyezah; Saeed, Sana (Journal of the Pakistan Medical Association, 2022)
This was a cross sectional study, conducted at the Aga Khan University, Karachi, from December 2018 to December 2019, to determine the residents' performance as teachers and understand the difficulties they faced. Anonymous feedback was obtained from students (n=200) to rate the teaching skills of residents in the paediatric department. The residents (n=60) also filled out an anonymous survey to assess their teaching performance and barriers to teaching. Furthermore, the faculty rated the residents' teaching abilities on a 5-point scale. A total of 145 (98.7%) students considered teaching as an important role of the residents. Ten (40%) residents identified themselves as beginners in teaching. The main barriers were time limitation (n=19, 76%), critical patients (n=3, 12%) and lack of appropriate skills (n=3, 12%). Keywords: Residency, Medical Students, Teaching, Faculty. Continue...